MicroRNA-20a-5p suppresses IL-17 production by targeting OSM and CCL1 in patients with Vogt-Koyanagi-Harada disease. Issue 2 (28th September 2017) - Chang, Rui; Yi, Shenglan; Tan, Xiao; Huang, Yang; Wang, Qingfeng; Su, Guannan; Zhou, Chunjiang; Cao, Qingfeng; Yuan, Gangxiang; Kijlstra, Aize; Yang, Peizeng
Abstract : Aim: To elucidate the role of microRNA-20a-5p (miR-20a-5p) in the pathogenesis of Vogt-Koyanagi-Harada (VKH) disease. Methods: Quantitative real-time PCR was used to quantify miR-20a-5p expression in CD4 + T cells from patients with active VKH and normal controls. The promoter methylation status of miR-20a-5p was detected by bisulfite sequencing PCR. Targets were evaluated by a luciferase reporter assay. The functional effects of miR-20a-5p on CD4 + T cells from patients with active VKH were assessed by upregulation or downregulation of its expression using liposomes. Results: The miR-20a-5p level was significantly decreased in CD4 + T cells from patients with active VKH as compared with normal controls. The two genes, oncostatin M (OSM) and C-C motif chemokine ligand 1 (CCL1), were identified as targets of miR-20a-5p. The upregulation of miR-20a-5p significantly suppressed interleukin 17 (IL-17) production in CD4 + T cells from patients with active VKH, whereas downregulation of miR-20a-5p exhibited an inverse effect. In addition, overexpression of OSM and CCL1 could rescue the effect of the upregulation of miR-20a-5p. Moreover, the level of miR-20a-5p was reduced in response to hypermethylation of the promoter. Further study showed that miR-20a-5p suppressed the activity of the phosphoinositide 3-kinase-AKT pathway. Conclusions: Our findings indicate that downregulation of miR-20a-5p is caused by promoter hypermethylation. MiR-20a-5p could also suppress the production of IL-17 by targeting OSM and CCL1 production in CD4 + T cells in patients with active VKH.